Veliki kormoran - Šorgo, Andrej (Acrocephalus, 1997)
5 Ictalurus nebulosus caught in half an hour by two Great Cormorants on 19th October 1995 at Pernica reservoir
Keywords: Great Cormorant; opazovanje; ornithology; ornitologija; Perniška akumulacija; Slovenia; veliki kormoran